Characters in Bakhtin's Theory - Anthony Wall (Studies in 20th & 21st Century Literature, 1984)
A common focus in many modern theories of literature is a reassessment of the traditional view of the character in a narrative text. The position that this article defends is that a revised conception is necessary for an understanding of the means by which dialogism is said to function in novelistic discourse. Revising the notion does not, however, involve discarding it outright as recent theories of the subject would have us do. Nor can we simply void it of all "psychological" content as suggested by many structuralist proposals. To retain Bakhtin's concept of the notion of character, we must understand the term "psychological" in the context of his early book on Freud. In artificially combining Bakhtin's isolated remarks on the literary character, we arrive at a view which postulates textualized voice-sources in the novel. In such a schema, maximum variability and freedom is afforded to each separate source. Yet we must use the term "separate" with extreme caution, for in Bakhtin's writings all those beings which we might wish to view as separate entities are in fact intricately intertwined and inseparable. Viewing something as absolutely separate implies knowing intimately all of its boundaries and possibilities. This is surely a capacity which Bakhtin would deny us when it comes to human figures in texts.
Keywords: Bakhtin; narrative; narrative structure; human figures; text; dialogue; dialogism; character; psychological; psychology; Freud